DUCK SYNDROME OF WORKING COLLEGE STUDENT : UNCOVERING THE ORGANIZATIONAL SUPPORT RELATIONSHIP WITH PSYCHOLOGICAL WELL BEING - Diny Atrizka; Ikbar Pratama; Hasrita Lubis (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the influence of organizational support and duck syndrome towards psychological well-being. It also seeks to determine whether duck syndrome mediates the relationship between organizational support and psychological well-being. A quantitative approach utilizing a total sampling technique was employed. The study involved 183 subjects—students who were also employed or we called as working college students. The research instruments included the Psychological Well-Being Scale, the Organizational Support Scale, and the Duck Syndrome Scale. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that duck syndrome mediates the relationship between organizational support and psychological well-being. Specifically, organizational support was found to have a significant positive direct effect on psychological well-being (β=0.488, T=5.42, p=0.001) but a negative effect on duck syndrome (β=-0.412, T=6.18, p=0.001). Duck syndrome was shown to mediate the relationship between organizational support and psychological well-being (β=0.301, T=3.27, p=0.001).